Potensi Tembakau Lembutan Temanggung Sebagai Indikasi Geografis Menurut Undang-Undang No 20 Tahun 2016 Tentang Merek Dan Indikasi Geografis - Indra Yuliawan; Setiawan Budi Santoso (International Forum of Researchers and Lecturers, 2023)
Temanggung Regency has an area of mostly highlands because it is located on the part of Mount Sindoro and Mount Sumbing. In general, these areas have lower temperatures and water is more limited than areas that are located lower, especially during the dry season. Not all types of plants can live and develop properly. One type of plant that can be cultivated with good results is tobacco. Initially, the tobacco grown in Temanggung Regency was N. tabacum var. fructicosa then became a variety that has been adapted for years to produce a specific tobacco quality. Through a special cultivation model, namely related to tillage, planting seeds, plant maintenance and fertilization, a long flat-shaped tobacco is produced with a width of approximately 0.5-1 cm. Therefore, people call it soft tobacco. Soft tobacco which is the original cultivation of the people of Temanggung is a special attraction for kretek products so that several manufacturers mix their products with soft tobacco from Temanggung Regency. Regardless of the pros and cons of the tobacco plant itself, Soft Tobacco can have economic value so it has potential to be used as a Geographical Indication for Temanggung Regency. This writing uses a qualitative method, with a normative juridical approach, in which case the method uses a statutory and conceptual approach. Protection of geographic indications aims to protect the uniqueness of a product, in this case, Temanggung soft tobacco from counterfeiting or improper use, while at the same time providing opportunity and legal protection to the people of the Temanggung area as producers of soft tobacco products to get maximum benefits. Therefore it is interesting to write about Soft Tobacco having the potential to become a Geographical Indication for Temanggung Regency and what is the role of the local government in making this Soft Tobacco a Geographic Indication.